2011
DOI: 10.1371/journal.pntd.0001364
|View full text |Cite
|
Sign up to set email alerts
|

Post-Treatment Follow-Up Study of Abdominal Cystic Echinococcosis in Tibetan Communities of Northwest Sichuan Province, China

Abstract: BackgroundHuman cystic echinococcosis (CE), caused by the larval stage of Echinococcus granulosus, with the liver as the most frequently affected organ, is known to be highly endemic in Tibetan communities of northwest Sichuan Province. Antiparasitic treatment with albendazole remains the primary choice for the great majority of patients in this resource-poor remote area, though surgery is the most common approach for CE therapy that has the potential to remove cysts and lead to complete cure. The current pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 41 publications
3
61
0
1
Order By: Relevance
“…The stage of the cyst is the variable most often investigated in correlation with serology results, with a consensus finding that patients with CE1 and CE4-CE5 (hepatic) cysts are seronegative in a high percentage of cases (30-58% and 50-87%, respectively), while rates of negativity are lower in the presence of CE2 and CE3 cysts (5-20%). 10,[12][13][14] When the variables associated with serology results were investigated in more detail, serodiagnosis performance correlated with stage, number (single versus multiple), location (liver versus lungs), and size (< or > than 15 cm) of cysts; presence of complications; and collection of serum after treatment. 10,11,13,15 Although in the majority of cases of hepatic CE the combined use of imaging and serology allows for a reliable diagnosis, in some instances they are inconclusive, and differential diagnosis with other lesions may be challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stage of the cyst is the variable most often investigated in correlation with serology results, with a consensus finding that patients with CE1 and CE4-CE5 (hepatic) cysts are seronegative in a high percentage of cases (30-58% and 50-87%, respectively), while rates of negativity are lower in the presence of CE2 and CE3 cysts (5-20%). 10,[12][13][14] When the variables associated with serology results were investigated in more detail, serodiagnosis performance correlated with stage, number (single versus multiple), location (liver versus lungs), and size (< or > than 15 cm) of cysts; presence of complications; and collection of serum after treatment. 10,11,13,15 Although in the majority of cases of hepatic CE the combined use of imaging and serology allows for a reliable diagnosis, in some instances they are inconclusive, and differential diagnosis with other lesions may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…10,[12][13][14] When the variables associated with serology results were investigated in more detail, serodiagnosis performance correlated with stage, number (single versus multiple), location (liver versus lungs), and size (< or > than 15 cm) of cysts; presence of complications; and collection of serum after treatment. 10,11,13,15 Although in the majority of cases of hepatic CE the combined use of imaging and serology allows for a reliable diagnosis, in some instances they are inconclusive, and differential diagnosis with other lesions may be challenging. This is particularly true in the case of small CE1 and old inactive CE4-CE5 cysts that may lack clear pathognomonic signs of echinococcal etiology on US and are serology negative in a high proportion of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Spleen (12) 77.7 (7) Splenectomy (6) Cystostomy and drainage (1) Bone (5) 100 (5) Debridement (3) Partial cystectomy and drainage (1) Mesentery (7) 85.1 (6) Small bowel resection (1) Cystectomy (5) Omentum (6) 100 (6) Cystectomy (6) Muscle (3) 100 (3) Cystectomy (3) Brain (2) 100 (2) Cystectomy (2) Adrenal (1) 100 (1) Cystectomy (1) Bladder (1) 100 (1) Cystectomy (1) Pancreas (1) 100 (1) Cystectomy (1) Turkiye Parazitol Derg 2017; 41: [28][29][30][31][32][33] Türkoğlu at al. Cystic Echinococcosis and lack of disease control programs (1,6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Another alternative is mebendazole, which is given at a daily dose of 40-50 mg/kg in three divided doses (6,26). It has been reported that the treatment response rate of 30% was achieved when patients were treated for 3-6 months, while the prolongation of treatment to up to 18-30 months accomplished a 32.7% decrease in the number of cysts and 49% cystic degeneration, which amounted to an overall response rate of 81% (26,29). The most important reason why albendazole treatment does not have the desired level of success is its poor absorptive capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The larval (metacestode) stage causes hydatidosis (cystic hydatid disease; cystic echinococcosis), a chronic cyst-forming disease in the intermediate (human) host. Currently, up to 3 million people are infected with E. granulosus 2,3 , and, in some areas, 10% of the population has detectable hydatid cysts by abdominal ultrasound and chest X-ray 4,5 .…”
Section: A R T I C L E Smentioning
confidence: 99%